2022
DOI: 10.3390/ma15062126
|View full text |Cite
|
Sign up to set email alerts
|

Orodispersible Films with Rupatadine Fumarate Enclosed in Ethylcellulose Microparticles as Drug Delivery Platform with Taste-Masking Effect

Abstract: Orally disintegrating (orodispersible) films provide a versatile tool for drug administration, especially in the pediatric and geriatric population, since they reduce the risk of choking and do not necessitate drinking water during application. By considering their direct contact with the taste buds, palatability is an influential aspect related to patient compliance. The microparticles based on taste-masking polymers containing drugs enclosed inside effectively mask the unpleasant taste of medicines. Ethylcel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…The taste masking effect of the obtained formulations was determined in vivo by a human taste panel and in vitro by a drug dissolution test. The formulation prepared with MP-A-RUP (F3) was rated as non-bitter to slightly bitter ( Table 2 ) compared to the formulation containing pure RUP (F2), which is in agreement with our previous results [ 26 , 30 ]. In the dissolution test, it was shown that formulation F2 released RUP very fast, whereas F3 was characterised by a much slower drug release ( Figure 3 ).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The taste masking effect of the obtained formulations was determined in vivo by a human taste panel and in vitro by a drug dissolution test. The formulation prepared with MP-A-RUP (F3) was rated as non-bitter to slightly bitter ( Table 2 ) compared to the formulation containing pure RUP (F2), which is in agreement with our previous results [ 26 , 30 ]. In the dissolution test, it was shown that formulation F2 released RUP very fast, whereas F3 was characterised by a much slower drug release ( Figure 3 ).…”
Section: Resultssupporting
confidence: 91%
“…Mats were tested in terms of tensile strength—TS, Young’s modulus—E, the percent of elongation at break—EB, and tear resistance—TR by a texture analyser (TA.XT plus, Stable Micro Systems, Godalming, UK). A piece of mat was placed in the bracket at a height of 20 mm and then extended with a 1 mm/s speed and a 5 kg cell loading [ 30 ]. Each study was performed at least in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar approach was used by Marzouk and co-workers [ 76 ] where the complexation of fluoxetine with β-cyclodextrins led to a taste-masking effect and also by Khan et al who focused on the developing of ODF with cefixime trihydrate and β -CD inclusion complexes [ 10 ]. Another example of manufacturing ODF with successful masking of the API bitter taste is the study of Olechno and co-workers [ 23 , 77 ]. An orally disintegrating film was developed with rupatadine fumarate in the form of ethylcellulose-based microparticles, using the solvent-casting method and electrospinning.…”
Section: Limitations Of Odf’smentioning
confidence: 99%
“…Improving the bioavailability of some APIs was a trigger for implementing solutions that enable controlling the rate of drug release. In this way, ODFs became a carrier for microparticles [ 23 ], nanoparticles [ 24 ], or nanocrystals [ 18 ], and self-emulsifying systems [ 25 ]. The development is also visible in another aspects, namely in manufacturing methods.…”
Section: Introductionmentioning
confidence: 99%